2017
DOI: 10.1016/j.adolescence.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related differences in social influence on risk perception depend on the direction of influence

Abstract: Adolescents are particularly susceptible to social influence. Here, we investigated the effect of social influence on risk perception in 590 participants aged eight to fifty-nine-years tested in the United Kingdom. Participants rated the riskiness of everyday situations, were then informed about the rating of these situations from a (fictitious) social-influence group consisting of teenagers or adults, and then re-evaluated the situation. Our first aim was to attempt to replicate our previous finding that youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 29 publications
8
83
2
4
Order By: Relevance
“…As a result, we cannot draw conclusions from the current study about whether the results are unique to prosocial behaviour (although studies indicate that age‐related decreases in social influence are seen for other types of behaviour too, such as risk perception and antisocial behaviour; Knoll et al., 2015, 2017; Steinberg & Monahan, 2007; Sumter et al., 2009). Further studies could assess how age affects prosocial, neutral and antisocial influence within the same paradigm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, we cannot draw conclusions from the current study about whether the results are unique to prosocial behaviour (although studies indicate that age‐related decreases in social influence are seen for other types of behaviour too, such as risk perception and antisocial behaviour; Knoll et al., 2015, 2017; Steinberg & Monahan, 2007; Sumter et al., 2009). Further studies could assess how age affects prosocial, neutral and antisocial influence within the same paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Linear mixed-effects models were used for all analyses. All statistical analyses were conducted in R (R Core Team, 2013) using lme4 (Bates, Mächler, Bolker, & Walker, 2014) and were based on the models used by Knoll and colleagues (Knoll et al, 2015;Knoll et al, 2017). Linear mixed effects models provide appropriate estimators for unbalanced designs (Schielzeth & Nakagawa, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most previous work has focused on how peers influence decisions towards making more risky decisions and therefore this finding might seem surprising at first. However, some studies that have looked at peer influence towards more safe decisions have shown that adolescents also conform towards safer decisions when a peer exhibits safer norms (Cascio et al., ; Knoll, Leung, Foulkes, & Blakemore, ). Similarly to risky decision‐making, the situations in which peers can move decisions towards safety is dependent on the type of peer influence and the type of decisions.…”
Section: Discussionmentioning
confidence: 99%